2023
DOI: 10.3389/fpls.2023.1271084
|View full text |Cite
|
Sign up to set email alerts
|

Construction of heat stress regulation networks based on Illumina and SMRT sequencing data in potato

Lina Shang,
Yonghong Zhou,
Shiqi Wen
et al.

Abstract: Potato (Solanum tuberosum L.) is one of the most important tuber food crops in the world; however, the cultivated potatoes are susceptible to high temperature, by which potato production is adversely affected. Understanding the coping mechanism of potato to heat stress is essential to secure yield and expand adaptability under environmental conditions with rising temperature. However, the lack of heat-related information has significantly limited the identification and application of core genes. To gain deeper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…A comprehensive understanding of the plant-specific chaperone network involving NudC proteins will further illuminate the molecular mechanisms of plant stress resilience. In addition to this, the advances in next-generation sequencing technologies have recently enabled the dissection of heat stress regulation modules [ 90 ]. Such thorough studies of the transcriptional signatures would shed light on the NudC gene coexpression networks in response to unfavorable conditions.…”
Section: Future Avenues Of Research On Nudc Proteins In Plantsmentioning
confidence: 99%
“…A comprehensive understanding of the plant-specific chaperone network involving NudC proteins will further illuminate the molecular mechanisms of plant stress resilience. In addition to this, the advances in next-generation sequencing technologies have recently enabled the dissection of heat stress regulation modules [ 90 ]. Such thorough studies of the transcriptional signatures would shed light on the NudC gene coexpression networks in response to unfavorable conditions.…”
Section: Future Avenues Of Research On Nudc Proteins In Plantsmentioning
confidence: 99%
“…Some others showed that genetic algorithms and particle swarm optimization might more effectively explore the hyperparameter space. Nevertheless, these methods may face early convergence and difficulty in handling the intricacies of real-time plant stress data 17 . A prospective way to cope with the challenge entails assessing blended optimization algorithms, particularly those that derive precedent from foraging behavior and search and rescue tactics.…”
Section: Introductionmentioning
confidence: 99%